Synthesis of Fatty Acid Methyl Esters from Jatropha curcas Oil and Its Purification Using Solvent Fractionation - Avita Kusuma Wardhani; Chusnul Hidayat (Indonesian Food and Nutrition Progress, 2014)
Fatty acid methyl esters (FAME) are produced by transesterification. The problem in the product of transesterification is the presence of impurities such as mono-, di-, triglycerides, and free fatty acids. So that, the purification using solvent fractionation is needed to separate them from FAME. The objective of this research were to determine the effects of crude fatty acid methyl esters-to-acetone (CFAME/acetone) ratio on yield, purity, purification factor, and recovery of FAME after fractionation and to evaluate the impurities which were separated in each step of fractionation. FAME were produced from Jatropha curcas oil using Berchmans’s and Tiwari’s methods. The impurities were separated by solvent fractionation using acetone. CFAME/acetone ratios were 1, 2, 3, 4, and 5. Fractionation was done stepwise namely 21°C, 16°C, 12°C, and 5°C. The results showed that the conversion of FAME using Tiwari’s method was 1.7-fold higher than Berchmans’s method. Purification of FAME using solvent fractionation resulted that the best CFAME/acetone ratio was 1. Yield decreased 1.6-fold at CFAME/acetone ratio 4. Purity decreased 8.74% with an increase in CFAME/acetone ratio 1 to 5. Purification factor decreased 2-fold at CFAME/acetone 1 to 3. Recovery decreased 1.3-fold at CFAME/acetone ratio 1 to 4. The impurities which were separated from FAME were mono-, di-, triglycerides, and free fatty acids and the major component of impurities was triglycerides (>59%). The results indicated that solvent fractionation could be used as an alternative method for purifying FAME and further study to optimize this method was needed.